The premature breech: caesarean section or trial of labour?. Issue 1 (March 1988) - Anderson, G; Strong, C
Abstract : Obstetricians face difficult decisions when the interests of fetus and mother conflict. An example is the problem of choosing the delivery method when labour begins prematurely and the fetus is breech. Vaginal delivery involves risks for the breech fetus of brain damage or death caused by umbilical cord compression and head entrapment. Caesarean section might avoid these dangers but involves risks for the mother, including infection, haemorrhage and even death in a small percentage of cases. If a caesarean section is performed the infant might die anyway, due to complications of prematurity. Thus, decisions about delivery method involve balancing the risks to mother and fetus. Uncertainty about the frequency of fetal injuries in vaginal breech deliveries adds to the difficulty of these decisions.